Thyroid-stimulating Hormone Response to Synthetic Thyrotrophin-releasing Hormone in Man. Issue 5704 (2nd May 1970) - Hall, R.; Amos, J.; Garry, R.; Buxton, R. L
Abstract : Synthetic thyrotrophin-releasing hormone, L-pyroglutamyl-L-histidyl-L-proline-amide, has been administered intravenously to euthyroid subjects in doses ranging from 1 to 200 μg. Its effect was assessed by serial measurements of serum thyroid-stimulating hormone (T.S.H.). A rise in serum T.S.H. was detectable five minutes after administration of 50 μg. of thyrotrophin-releasing hormone, reaching a maximum in 15 to 30 minutes, and then gradually declining over the next 120 minutes. Doses of 100 and 200 μg. of thyrotrophin-releasing hormone produced even greater rises of T.S.H. in some cases. The only side-effect noted was transient nausea with doses greater than 50 μg. Measurement of serum T.S.H. levels after administration of thyrotrophin-releasing hormone should prove a useful test of pituitary T.S.H. release and may help to distinguish pituitary and hypothalamic lesions.